Cephalometric Antero-Posterior Parameter Evaluation in Orthodontic Patients with Facial Asymmetries - Szuhanek C; Nagib R; Sabo-Meze A; Buzatu R; Malita D (Journal of Dentistry And Oral Implants, 2020)
Aesthetic and functional problems associated with significant facial asymmetry can negatively affect the patient's facial appearance, nutritional and psychosocial development. Therefore, a critical assessment and accurate treatment planning is absolutely necessary. The aim of this study was to evaluate the parameters of PA cephalometric analysis defined by Ricketts and Grummons and establish statistically relevant correlations and their importance in diagnosing orthodontic patients with varying degrees facial asymmetries. The research included facial asymmetry Romanian patients from the Department of Orthodontics and Dento-Facial Orthopedics of UMF
Keywords: Facial asymmetries